Analisa Pengaruh Perbedaan Winding terhadap Back EMF dan Ke pada PMSG 18s16p - Ibnu Aqil Albarohin; Ulinnuha Latifa (PTE FTK UIN Ar-Raniry, 2021)
Electrical energy depends on the non-renewable natural resources which depletion all year. It has been a reason to run the research about renewable energy. In terms of renewable energy, wind power, has various types of wind turbines which able to produce quality new renewable electrical energy. The problems should be assessed was how to wind a coil or winding in a generator needs. It was important to result a good quality wind turbine. From this study, there are 2 winding options on the PMSG 18s16p which have same winding direction for each coil with average tension. This winding obtained about 4.188 V. The second option was the winding which has an average voltage value of 4.762 V but the windings stand in the opposite direction for some coils. It should been considered by an engineer if the use of generator to produce a larger output. On the other hand, to make easier manufacturing, the next study must sacrifice the resulting output.